2009
DOI: 10.1302/0301-620x.91b1.21026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an associated ulnar styloid fracture on the outcome after fixation of a fracture of the distal radius

Abstract: A total of 118 consecutive patients with a fracture of the distal radius were treated with a volar locking plate; 50 patients had no ulnar styloid fracture, 41 had a basal ulnar styloid fracture, and 27 had a fracture of the tip of the ulnar styloid. There were no significant differences in radiological and clinical results among the three groups. The outcome was good and was independent of the presence of a fracture of the ulnar styloid. A total of five patients (4.2%) had persistent ulnar-sided wrist pain at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 42 publications
7
92
3
1
Order By: Relevance
“…Only one had a Gustilo grade I open wound on the volar aspect. Seven of the fractures had associate fracture of the ulnar styloid but none underwent any operative treatment as it has been shown that the functional outcome was good even though the ulnar styloid was not operated 21 . In all but two fractures the index procedure was volar locking plate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one had a Gustilo grade I open wound on the volar aspect. Seven of the fractures had associate fracture of the ulnar styloid but none underwent any operative treatment as it has been shown that the functional outcome was good even though the ulnar styloid was not operated 21 . In all but two fractures the index procedure was volar locking plate.…”
Section: Resultsmentioning
confidence: 99%
“…It had been clearly mentioned that the presence of ulnar styloid fracture does not adversely affect the outcome in patients with a fracture of the distal radius treated by volar locking plating. 21 Limitations of our study include its lack of controls and relatively small number of cases. …”
Section: Discussionmentioning
confidence: 97%
“…The authors did not specifically assess DRUJ instability before or after surgery. Zenke et al 16 reported a case series of 118 distal radius fractures treated with volar plating, 68 with and 50 without ulnar styloid fractures. The authors found higher rates of ulnar-sided wrist pain in those with increased initial ulnar variance but no differences in ulnar-sided wrist pain, range of motion, or grip strength based on presence, size, or displacement of a styloid fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its anatomic proximity to the triangular fibrocartilage complex, fracture of the ulnar styloid at its base has been postulated to cause DRUJ instability [12,28,33,37]. However, well-designed studies consistently denied the association between symptomatic DRUJ instability and the ulnar styloid fracture in distal radius fractures [15,35,39,44]. Recently widening of the DRUJ gap was identified as an independent risk factor for DRUJ instability in distal radius fractures [8].…”
Section: Discussionmentioning
confidence: 99%
“…The ulnar styloid fractures, especially at the base with greater than 2 mm of displacement, have been regarded as the risk factor for DRUJ instability in distal radius fractures [37] because of its proximity to the deep triangular fibrocartilage complex [32]. However, it still is unclear whether the displaced ulnar styloid fractures cause pain and instability at the DRUJ in patients with distal radius fractures [34,40,44]. One study suggested that stable internal fixation of distal radius fractures results in a stable DRUJ after bony healing regardless of the presence of substantially displaced, unrepaired ulnar styloid fractures [39], whereas two studies [15,35] reported no differences in the wrist function between patients with unrepaired ulnar styloid fractures and those without ulnar styloid fractures.…”
Section: Introductionmentioning
confidence: 99%